2007
DOI: 10.1159/000111783
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Otological Findings in Patients with Migraine- and Nonmigraine-Related Dizziness

Abstract: This study presents the neuro-otological findings of 523 patients attending a tertiary vestibular clinic with migraine- and nonmigraine-related dizziness. Subjects were categorized into one of 4 groups, definite migrainous vertigo, probable migrainous vertigo, vestibular disorder coexisting with migraine and nonmigraine-related dizziness. No notable relationship was found between the numbers of abnormal findings between the groups for the majority of the neuro-otological tests. However, there was a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 95 publications
6
55
0
Order By: Relevance
“…The high prevalence at follow-up agrees with previous findings [5], whereas the low prevalence at initial presentation is comparable to the results of recent studies that reported around 8 and 16.6% [8,9,10]. Thus, the clear-cut increase in central ocular motor findings at follow-up explains well the different results reported in earlier studies as being due to a time bias.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high prevalence at follow-up agrees with previous findings [5], whereas the low prevalence at initial presentation is comparable to the results of recent studies that reported around 8 and 16.6% [8,9,10]. Thus, the clear-cut increase in central ocular motor findings at follow-up explains well the different results reported in earlier studies as being due to a time bias.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, current studies that included patients with migraine and vertigo according to the Neuhauser criteria showed different results. One study reported central ocular motor disturbances in 16.6%, while two other studies reported central ocular motor signs in only about 8% of patients with VM [8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Such findings, however, are not specific for vestibular migraine, because they can be found also in migraine patients without vestibular symptoms and in many other vestibular syndromes 37 . In one study, patients with vestibular migraine became nauseous after caloric testing four times more often than migraine patients and patients with other vestibular disorders 38 . A neuro-otologic study of 20 patients during the acute phase of vestibular migraine showed pathological nystagmus in 14 patients, mostly central spontaneous or positional nystagmus.…”
Section: Clinical Presentationmentioning
confidence: 97%
“…Oculographic studies may show evidence of central-vestibular dysfunction with acute migrainous vertigo [23]. No specific neurootologic abnormality has been linked to MAV although patients with MAV were 4 times more likely to develop nausea with caloric stimulation [24]. In the absence of a confirmatory diagnostic test, the diagnosis of MAV is based on clinical criteria [25].…”
Section: Diagnosticsmentioning
confidence: 99%